The Indonesian Government's Dilemma between National Law and International Law in the Nickel Dispute - Khairus Febryan Fitrahady (Intellectual Law Review (ILRE), 2025)
Indonesia possesses the world’s largest nickel reserves, estimated at around 21 million tonnes or approximately 30% of total global reserves, positioning nickel as both a strategic national asset and a crucial instrument in international economic relations. Recognising its importance, the Indonesian government introduced a down streaming policy by prohibiting raw nickel ore exports beginning in 2019. This measure is designed to increase domestic value-added production, enhance economic sovereignty, and fulfil the constitutional mandate of Article 33 of the 1945 Constitution. Employing a normative juridical method with legislative, conceptual, and case approaches, this study examines the conflict between Indonesia’s domestic legal framework and international trade law in the context of the nickel dispute at the World Trade Organization (WTO). The analysis reveals that while the down streaming policy has yielded significant benefits, such as higher exports of processed products and increased state revenues, Indonesia also faces challenges following the European Union’s successful claim at the WTO. The export ban was deemed to contravene Article 11 of GATT 1994. This dispute underscores the dilemma between sovereign rights over natural resource management and compliance with international trade obligations. The study concludes that reconciling sovereignty with international commitments requires harmonisation through legal, economic, and diplomatic strategies